Aqueous dispersion and tuning surface charges of polytetrafluoroethylene particles by bioinspired polydopamine–polyethyleneimine coating via one-step method. Issue 8 (4th August 2021) - Grewal, Manjit Singh; Abe, Hiroya; Matsuo, Yasutaka; Yabu, Hiroshi
Abstract : We propose a surface modification of poorly dispersive polytetrafluoroethylene (PTFE) particles via bioinspired polydopamine–polyethyleneimine (PDA–PEI) which conferred PTFE particles a uniform dispersion in aqueous medium. With increasing dopamine concentration in the reaction solution, dispersity of PTFE particles improved and the surface charges of particles changed from negative to positive due to an increase of surface coverage of PDA–PEI layers. Simplicity of the method here outlines an attractive route for surface modification of inert surfaces useful for large-scale applications.